A D-Band Direct-Conversion IQ Receiver with 28 dB CG and 7.3 dB NF in 130 nm SiGe Process - Fei He; Yuhan Ding; Zhongchen Xu; Menghu Ni; Yibo Tian; Zhenyi Zhang; Zhixiang Shi; Kailei Wang; Qian Xie; Zheng Wang (Micromachines, 2022)
In this paper, a D-band direct conversion IQ receiver with on-chip multiplier chain is presented. The D-band LNA with gain-boosting and stagger-tunning technique is implemented to provide high gain and large bandwidth. X9 multiplier chain including Marchand balun and quadrature (90°) hybrid is employed to provide four path LO signal to drive IQ mixer. This receiver is implemented in a 130nm SiGe process and consumes a core area of 1.04 mm2. From the experimental results, the proposed receiver exhibits a 20 GHz bandwidth from 150 GHz to 170 GHz, with CG of 28 dB and NF of 7.3 dB at 158 GHz.